2008
DOI: 10.1007/s00428-008-0594-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 expression is induced by viral BARF1 and is overexpressed in EBV-associated gastric cancer

Abstract: Approximately 10% of gastric carcinomas (GC) worldwide are associated with Epstein-Barr virus (EBV). GC is one of the most frequent human malignancies associated with EBV. The latent expression of the EBV-oncogene BARF1 is restricted to epithelial malignancies. To investigate the underlying BARF1-related mechanisms of oncogenic epithelial transformation, we analyzed gene expression profiles of a BARF1-transfected epithelial (HaCaT+) and the corresponding BARF1-negative (HaCaT-) cell line by cDNA microarray ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…However, although the differences did not reach a significant level, the frequency of cyclin D1 overexpression was higher in the gastric phenotype than in the intestinal and mixed phenotypes. Cyclin D1 was previously studied in several series of gastric cancers, with a reported frequency of 20~56% of overexpression being reported [27-29], different from our results. As a possible reason for these differences of cyclin D1 overexpression, although early differentiated-type cancers, except for gastric phenotype, do not require an increase of cyclin D1, once the tumor has developed, the tumor cells need a high level of cyclin D1 for tumor progression.…”
Section: Discussioncontrasting
confidence: 99%
“…However, although the differences did not reach a significant level, the frequency of cyclin D1 overexpression was higher in the gastric phenotype than in the intestinal and mixed phenotypes. Cyclin D1 was previously studied in several series of gastric cancers, with a reported frequency of 20~56% of overexpression being reported [27-29], different from our results. As a possible reason for these differences of cyclin D1 overexpression, although early differentiated-type cancers, except for gastric phenotype, do not require an increase of cyclin D1, once the tumor has developed, the tumor cells need a high level of cyclin D1 for tumor progression.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study showed an increase in NF-B and cyclin D1 expression in BARF1-expressing cells but not in mock-transfected cells. This is consistent with the results of Wiech et al (40). They reported BARF1-induced cyclin D1 upregulation in gastric carcinoma, citing our previous data that cyclin D1 immunostaining was more frequently positive in EBV-positive gastric carcinomas than in EBV-negative gastric carcinomas (9).…”
Section: Discussionsupporting
confidence: 93%
“…For example, BARF1, which is exclusively expressed in EBV-associated GCs, has oncogenic properties in many cell types such as monkey kidney epithelial cell line [6] and human B lymphocytes [7], and human epithelial cell line HBE [8]. In addition, cyclin D1 induced in BARF1-transfected epithelial cells was overexpressed in EBV-associated GCs, indicating an interaction of viral BARF1 and cyclin D1 [9]. However, BARF1 transcripts have never been shown to produce protein in EBV-positive GCs.…”
Section: Introductionmentioning
confidence: 99%